FRACTAL AS FORM GENERATOR CASE STUDY: TSUNAMI MEMORIAL PARK - Lukman, Muhamad
The Thesis explores the possibility of using the Mathematica Theory, particularly in Fractal Theory, to help designer exploring the possibilities and choices of designs, providing solutions for problems, and giving new tool and criteria in designings. In this thesis, Tsunami Memorial Park is chosen as a case study for this theory. Reason to use this case study is because the student’s participation of Tsunami Memorial Park Competition held by Thailand Government. The competition aims to develop a place for remembering the Tsunami and the aftermath. The competition also proposes a place for learning. The Memorial will be situated in Khao Lak Lamru National Park. The dense vegetation of this place requires specific attention towards conservation issue and sensitivity in designing as part of natural landscape. The Fractal Theory is being used to design The Memorial. Fractal Theory in definition is a theory to describe and builds shapes that has many resemblance with nature. The reason to use Fractal Theory is because the appropriateness of this theory to produce shapes found in nature and the issue of harmonisation between human and nature. Methods used for thesis comprise of three parts. The first is Wavelet Analysis. This method analyses one dimensional graphic as an input and elements to build the graphic as an output. Wavelet Analysis is used as a tool for considerating the placement of the building in the site. The site’s silhouette line is then processed by this method to produce elements that makes the line. By using these elements derived from the site the harmony of the entire site will remain. The second method is Cellular Automata. This method reorganize the units that build certain shapes. After finding the site for the building, designer then takes the three dimensional data of the particular two dimensional data by adding the height of the site. This method then assigns general characteristics and certain rule to each unit. The method then evaluates the element and produce new shapes used for forms of architecture. The third method is Fractal Dimension Analysis. The method analyses the fractal character of the site from certain view. The character is named Fractal Dimension. If the dimension of the site before and after the architecture is build remains relatively the same then it can be said that the architecture has the same Fractal Dimension of the site. In this thesis, the designer analyses the site for obtaining the best location for the architecture. The designer doing so by making many sections from the site. These sections are then to be translated as one dimensional curve of silhouette line of the site. The lines then are then deconstruct by Wavelet Analysis to their elements. Section that produces interesting elements by the designer’s point of view is then chosen as the building’s site. Besides that factor, the architectural point of view are also considered. These elements are then processed to produce architectural form. In this case these one dimensional lines are processed to produce three dimensional mesh by aid of AutoCad. The forms produce are roof, lower floor and glass frame made from line of the elements. For making columns and floor plate the designer uses Cellular Automata System. The site where the architecture is going to be build is excavated to produce three dimensional data of the site. The site is then processed as units that forms it. These units are then assigned by characters and then evaluated. The process of birth and evaluation produces new forms used to form the architecture. Designs that uses Fractal Theory produces forms that enrich the choices of designs. The use of Wavelet Analysis and Cellular Automata also produces specific form for each site. Fractal Dimension Analysis can also be used as new design criteria in architecture and evaluation process.